Study on test of coal co-firing for 600MW ultra supercritical boiler with four walls tangential burning - Ying Wu; Yong-lu Zhong; Guo-mingi Yin (E3S Web of Conferences, 2018)
On account of nine commonly used coals in a Jiangxi Power Plant,two kinds of coal were selected to be applied in coal co-firing test through industrial analysis,elementary analysis and thermogravimetric analysis of coal.During the coal co-firing test,two load points were selected,three coal mixtures were prepared.Moreover,under each coal blending scheme, the optimal oxygen content was obtained by oxygen varying test. At last,by measuring the boiler efficiency and coal consumption of power supply in different coal co-firing schemes, the recommended coal co-firing scheme was obtained.